EFFECTIVENESS OF GRAPHIC DESIGN PLATFORMS AS LEARNING MEDIA IN VOCATIONAL EDUCATION: A PRISMA-BASED SYSTEMATIC LITERATURE REVIEW - Deny Fathur Rachman Sugi Harto; Syamsul Hadi; Dani Irawan; Erwin Komara Mindarta (RADJA PUBLIKA, 2026)
This study aims to analyze the effectiveness of graphic design platforms as learning media in vocational education through a systematic literature review based on the PRISMA framework. In the context of accelerating digital transformation in education, particularly in vocational schools, there is a growing need for visual, interactive, and technology-supported learning environments to enhance students’ learning experiences and competencies. This study systematically reviewed 50 peer-reviewed journal articles published between 2004 and 2025, retrieved from Scopus, Google Scholar, and ScienceDirect databases. The selection process followed the PRISMA stages, including identification, screening, eligibility, and inclusion. Data were analyzed using a descriptive-comparative approach and synthesized using vote-counting techniques to identify dominant research patterns. The findings indicate that graphic design platforms—such as Canva, Adobe Illustrator, and similar tools—consistently contribute to improved learning outcomes (86%), increased student engagement (80%), and enhanced conceptual understanding (76%). Recent studies (2025–2026) also emphasize the increasing role of AI-integrated design tools in improving usability, creativity, and instructional efficiency in education settings . These results confirm that graphic design platforms are not merely technical tools but strategic learning media that strengthen visual cognition, learner interaction, and instructional clarity. The study concludes that integrating graphic design platforms into vocational education significantly enhances learning effectiveness, particularly in terms of engagement, comprehension, and academic performance.